Fabrication and antimicrobial analysis of composite biodegradable film from chempedak seeds - Syamsutajri, Syamsol Bahri (2010)
Chempedak seed flour is a starchy material with low-cost. Films carrying antimicrobial agent has been the most potential type of packaging in industry. The most suitable additives have not yet discovered but starch films have been widely researched. Chempedak seed starch film has been the best source as it has organic fibers to enhance the film. The aim of this study were to develop antimicrobial biodegradable films based on chempedak seed flour, and to characterize their morphology, physical and mechanical properties. Films were prepared by casting method. The preparation of films include of the preparation of chempedak seed flour, isolation of the starch and preparation of solution at temperature range of 80°C to 100°C. Fourier transform infra-red (FT-IR) spectra analysis revealed that starch crytallinity was retarded with chitosan incorporation and that hydrogen bonds were formed between chitosan and starch at wavelength 34003600 cm -1. Films incorporated with 2% chitosan have lower water solubility which was 27.76% and higher viscocity (428.9 cP) at 10 rpm while SEM micrograph of the film obviously showed insoluble starch granule. The antimicrobial activities of films were examined against E. coli and B. subtilis. Stronger bacterial effects showed with B. subtilis than E. coli in the presence of 2% chitosan. TS were increase ith the increasing of chitosan incorporation. As a conclusion, the case studies on the analysis of antimicrobial activity of chempedak seed biodegradable film incorporated with chitosan could be used as an alternative to starch for biodegradable film. Furthermore, the films exhibit good antimicrobial activity which can help extend the food shelf life.